A COGNITIVE-DISCURSIVE ANALYSIS OF INFORMATION ERRORS IN MASS MEDIA (International journal of artificial intelligence, 2026)
This article analyzes cognitive and discursive aspects of information errors in mass media within the framework of academic approaches developed at the Uzbekistan University of Journalism and Mass Communications. The study examines errors arising in the processes of information production and dissemination, focusing on cognitive factors related to human thinking as well as the discursive features of media texts. In particular, the influence of cognitive biases such as confirmation bias and framing effect on the misinterpretation of journalistic content is explored. Furthermore, through discourse analysis, semantic shifts, contextual distortions, and manipulative strategies in media texts are identified. The findings of the study contribute to enhancing information credibility in mass media and provide scientific insights into reducing information errors.